(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study examined the major activities and production trends of artisanal fish farming among communities along the River Niger using survey data collected in 2025. Descriptive statistics were employed to analyse respondents’ perceptions. Findings reveal that artisanal fish farming is a key livelihood activity, with 83% of respondents agreeing that it constitutes their primary source of income. Traditional fishing methods remain dominant, as indicated by 81% agreement, while 72% reported reliance on natural water bodies for fish breeding and rearing. However, 74% acknowledged a gradual increase in the use of modern aquaculture techniques. Fish preservation and processing practices were less consistent, with 68% participation and 29% indicating non-involvement. Regarding production trends, 90% of respondents observed a significant increase in fish production over the past five years, while 82% agreed that available resources support high production levels. Furthermore, 87% reported year-round fish availability, and 82% indicated that supply meets local demand. Notably, 87% affirmed that the River Niger still provides abundant fish resources. The study concludes that artisanal fish farming remains vital and moderately evolving, though constrained by limited modernization and infrastructural gaps, highlighting the need for sustainable management and technological advancement.